2021
DOI: 10.3389/fenvc.2021.672250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Manganese Oxide Octahedral Molecular Sieves for CO and C3H6 Oxidation at Diesel Exhaust Conditions

Abstract: Mn-based materials have been widely applied in the environmental catalysis field for their excellent redox properties. Here, three kinds of crystallite manganese oxides (pyrolusite, cryptomelane and todorokite) with different tunnel sizes (MnO(1 × 1), MnO(2 × 2), and MnO(3 × 3)) were prepared by hydrothermal method, and their catalytic performance in complete oxidation of diesel vehicle exhaust were tested. The highest catalytic oxidation activity was achieved on MnO(3 × 3) when compared with that on MnO(1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Figs. 10 and 11 shows the C 3 H 6 and CO oxidation investigations of the prepared manganese oxides [94]. These results are supported by another report, which is allied with the catalytic action of manganese oxide nanoparticles with tunnel structure and cation present in them [95].…”
Section: Catalystsupporting
confidence: 71%
See 1 more Smart Citation
“…Figs. 10 and 11 shows the C 3 H 6 and CO oxidation investigations of the prepared manganese oxides [94]. These results are supported by another report, which is allied with the catalytic action of manganese oxide nanoparticles with tunnel structure and cation present in them [95].…”
Section: Catalystsupporting
confidence: 71%
“…Owing to their excellent redox properties, manganese oxide nanomaterials have been extensively used as catalysts. To evaluate the catalytic performance, Wang et al [94] synthesized manganese oxide nanomaterials having various tunnel sizes [pyrolusite:(1 1), cryptomelane:(2 2) and todorokite:(3 3)] by hydrothermal method and examined the complete oxidation of diesel vehicle exhaust. It had been observed that with exclusive structure, greater specific surface area and enhanced redox properties, the greatest catalytic oxidation ability has been exhibited by manganese oxide (3 3) among these three structures.…”
Section: Catalystmentioning
confidence: 99%
“…, and [3-0-1] hkl planes of the tetragonal unit cell of β-MnO 2 , respectively [53][54][55][56]. The observed XRD pattern could be radially indexed to tetragonal MnO (1 × 1) pyrolusite (β-MnO 2 ) (JCPDS 24-0735) [41]. The lattice parameters (a, b, c), Miller indices (h, k, l), and interplanar spacing (d hkl ) for the tetragonal unit call are related as given in Equation ( 1).…”
Section: Characterizationmentioning
confidence: 99%
“…The crystalline phase of manganese oxides in all three structures consists of [MnO 6 ] octahedral units. The 1D tunnel structure of manganese oxide, called manganese oxide octahedral molecular sieve, has received extensive attention due to its superior catalytic performance [38][39][40][41]. There are three tunnel structures of manganese oxides called todorokite, cryptomelane, and pyrolusite (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental contamination, the use of lubricants in harvesting and food production machinery, and packaging can also cause food contamination from mineral oils and hydrocarbons (Grob, 2018). Additionally, enteric methane (CH 4 ) is a short-lived climate pollutant with a warming effect 34 times greater than carbon dioxide.The damage to the ozone layer and human health caused by the presence of gaseous hydrocarbons in the atmosphere, such as methane, benzene, and various polycyclic aromatic hydrocarbons, in addition to the contamination of soil and air due to hydrocarbon leaks from oil and gas plants and the emission of methane into the air and mineral oil hydrocarbons in the food industry, highlight the urgent need for the development of sensitive hydrocarbon detection techniques (Sampaolo et al, 2020;Wang et al, 2021;Martínez-Álvarez et al, 2022). Several methods have recently been demonstrated for hydrocarbon detection, including real-time polymerase chain reaction, genome sequencing-based techniques, hyperspectral remote sensing, reflectometric biosensing, optical spectroscopy, laser absorption spectroscopy (LAS), photoacoustic spectroscopy (PAS), and gas chromatography combined with various techniques such as mass spectrometry, vacuum ultraviolet detection, and flame ionization detection (…”
mentioning
confidence: 99%